Abiraterone Treatment in Castration-Resistant Prostate Cancer Selects for Progesterone Responsive Mutant Androgen Receptors - Chen, Eddy J.; Sowalsky, Adam G.; Gao, Shuai; Cai, Changmeng; Voznesensky, Olga; Schaefer, Rachel; Loda, Massimo; True, Lawrence D.; Ye, Huihui; Troncoso, Patricia; Lis, Rosina L.; Kantoff, Philip W.; et al. (Clinical cancer research, 2015)
Purpose: The CYP17A1 inhibitor abiraterone markedly reduces androgen precursors and is thereby effective in castration-resistant prostate cancer (CRPC). However, abiraterone increases progesterone, which can activate certain mutant androgen receptors (AR) identified previously in flutamide-resistant tumors. Therefore, we sought to determine if CYP17A1 inhibitor treatment selects for progesterone-activated mutant ARs. Experimental Design: AR was examined by targeted sequencing in metastatic tumor biopsies from 18 patients with CRPC who were progressing on a CYP17A1 inhibitor (17 on abiraterone, 1 on ketoconazole), alone or in combination with dutasteride, and by whole-exome sequencing in residual tumor in one patient treated with neoadjuvant leuprolide plus abiraterone. Results: The progesterone-activated T878A-mutant AR was present at high allele frequency in 3 of the 18 CRPC cases. It was also present in one focus of resistant tumor in the neoadjuvant-treated patient, but not in a second clonally related resistant focus that instead had lost one copy of PTEN and both copies of CHD1. The T878A mutation appeared to be less common in the subset of patients with CRPC treated with abiraterone plus dutasteride, and transfection studies showed that dutasteride was a more potent direct antagonist of the T878A versus the wild-type AR. Conclusions: These findings indicate that selection for tumor cells expressing progesterone-activated mutant ARs is a mechanism of resistance to CYP17A1 inhibition. Clin Cancer Res; 21(6); 1273–80. ©2014 AACR. See related commentary by Sharifi, p. 1240